Utilization of indonesian megabiodiversity for integrated science learning with nationalism values to develop concepts understanding and soft security among students of border areas - Sukardiyono Sukardiyono; Dadan Rosana (Universitas Negeri Yogyakarta, 2018)
This research aimed at (1) producing Subject Specific Pedagogic (SSP) of integrated science learning with nationalism values by utilizing Indonesian megabiodiversity which is valid and practical for the students of border areas, (2) obtaining empirical test results on the effectiveness of SSP integrated science learning with nationalism values by utilizing Indonesian megabiodiversity to improve the quality of students’ learning outcomes and soft security in border area. The SSP was prepared through a research design referring to